EFEKTIVITAS MEDIA FLASH CARD BERBASIS MICROSOFT POWERPOINT PADA KETERAMPILAN MEMBACA NYARING KELAS II DI SD NEGERI 1 BANDENGAN - Yanicha Rosalia Amanda; Wawan Priyanto; Kartinah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effectiveness of using Microsoft PowerPoint-based flash card media on the oral reading skills of second-grade students at SD Negeri 1 Bandengan. The background of the study stems from the low oral reading skills of students, as indicated by inaccurate pronunciation, improper intonation, low volume, and lack of reading fluency. This research employed a quantitative method with a one-group pretest-posttest design. The sample consisted of all 35 second-grade students. Data collection instruments included oral reading tests, observation sheets, and student questionnaires. Data were analyzed using normality tests, paired sample t-tests, and N-Gain analysis. The results showed an increase in students’ oral reading scores, with a pretest average of 59.14 and a posttest average of 80.14. The paired sample t-test indicated a significance value of 0.000 (p < 0.05), meaning there was a significant difference before and after the treatment. The N-Gain score was 0.51, categorized as moderate. Based on these findings, it can be concluded that the use of Microsoft PowerPoint-based flash card media is effective in improving the oral reading skills of second-grade students.